MULTICULTURAL VALUES IN GONTOR 9 ISLAMIC BOARDING SCHOOL LAMPUNG - INDONESIA - DERMAWAN, OKI (Universitas Islam Negeri Raden Intan Lampung, 2017)
Indonesia is one of the most multicultural countries in the world. This fact can be seen from the sociocultural and geographically so diverse and widespread. Multicultural education offers an alternative through the implementation of educational strategies and concepts based on the utilization of the diversity that exists in society, especially for the students such as have ethnic diversity, culture, language, religion, social status, gender, ability, age, etc.. In multicultural education, teachers are not only required to master but also teach professionally the subjects taught. More than that, an educator must also be able to instill the values of multicultural education such as democracy, humanism, and pluralism as well as instill religious values to the students. In turn, the resulting out-put of the school are not only proficient in accordance with the disciplines practiced, but also able to apply the values of understanding and respect for diversity. Keywords: multicultural education, diversity and religious